Evaluasi Sistem Informasi Manajemen Puskesmas (Simpus) (Studi Kasus : Puskesmas Induk Di Wilayah Kabupaten Sukoharjo) - Dasa Styo Ndaru Utomo; Sri Hariyati Fitriasih; Setiyowati Setiyowati (Jurnal Teknologi Informasi dan Komunikasi (TIKomSiN), 2021)
The public health center management information system (SIMPUS) is used to provide services at public health center, from patient registration to medical services. There are some inconsistencies regulations happen, so it is needed evaluation using COBIT 4.1 to evaluate the level of capability (As-Is) and draw conclusion.This research uses primary and secondary data collection methods. This study uses primary and secondary data collection methods. The author conducts an evaluation process using Framework COBIT 4.1 domain Acquire and Implement (AI) process Acquire and Maintain Application Software (AI2), Delivery and Support (DS) process Educate and Train Users (DS7) and Monitor and Evaluate (ME) process Monitor and Evaluate IT Performance (ME1). There are 154 respondents with details of AI2 27 respondents, DS7 100 respondents, and ME1 27 respondents. The AI2 questionnaire has 24 questions, DS7 and ME1 have 18 questions. The maturity level of AI2 is 3.29 and DS7 is 2.59, the value of CO maturity is at matury level 3, which means the condition in which the entire process has been documented and has been communicated, and implemented properly, but there is no evaluation process of the system. The ME1 maturity level of 3.58 at matury level 4 means that the computerized process can be monitored and evaluated properly. Based on the expected level, it is concluded that the average expected ideal value for AI2 and DS7 is at level 4 while ME1 is at level 5.